THE GENERALITY OF NEUROBIOLOGICAL PROCESSES IN THE CNS DISORDERS - D. V. Blinov (Эпилепсия и пароксизмальные состояния)
Generality of neurobiological processes in the most common CNS disorders could be verified. Thus, the acute pathology of the nervous system is accompanied by increased permeability ("breakthrough") of blood-brain barrier (BBB), which is trigger for inclusion of autoimmune mechanisms. This is often requiring a chronic neurodegenerative process. In particular, elevated levels of neuron specific antigens (NSA) in the peripheral blood could be causes the synthesis of correspond antibodies and secondary violation of BBB permeability which has autoimmune reasons. Dysfunction of CNS neutransmitter systems accompanies by chronic diseases. Often this is a consequence of primary damage to the nervous tissue in violation of the BBB resistance. Bu-turn, this has an impact on the BBB condition. Further investigations of these pathogenetic aspects that are common to a large number of CNS diseases, will strengthen the importance of an integrated approach in the treatment and prevention.